Coverage Bias by Medcom and Media Indonesia toward Anies Baswedan in the 2024 Presidential Election - Fida Ul Haq, Muhammad; Shobrina Imamah, Nurul; Gomo Attas, Siti; Anoegrajekti, Novi (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
Norman Fairclough's Critical Discourse Analysis (CDA) is one of the discourse analysis methods that can be applied to examine a discourse or text, whether on a small or large scale. Fairclough's CDA emphasizes the process of text production, the dissemination of the text, and its socio- economic-cultural aspects. This approach dissects discourse from micro to macro dimensions, in line with the complexity of the issues at hand. The research aims to understand several news articles presented by Medcom and Media Indonesia regarding the activities of Anies Baswedan leading up to the 2024 presidential election. The research method applied is qualitative, utilizing text analysis with the transitivity of Systemic Linguistic Functional (SFL) approach. The results of the analysis indicate a tendency in the four news articles to present a positive image of Anies Baswedan.